Integrated management of pod rot disease of cocoa in hilly tracts of Karnataka - Hegde, Gurudatt M. (Journal of Plantation Crops, 2020)
Cocoa suffers heavily due to pod rot disease caused by Phytophthora palmivora, causing yield losses ranging from 30 to 60 per cent. For devising strategies for effective management of pod rot disease, the present study was conducted during Kharif seasons of 2012-13 and 2013-14 in farmer’s field in the hilly tracts of Uttara Kannada district of Karnataka State, India. The results revealed that sequential spray of Metalaxyl MZ 68WP at 0.2 per cent followed by 1 per cent Pseudomonas fluorescens at 15 days interval significantly reduced the severity of pod rot disease (20.1%) in cocoa. This was followed by spraying of Mancozeb at 0.25 per cent + P. fluorescens at 1 per cent and spraying of Bordeaux mixture (1%) + P. fluorescens at 1 per cent. The reduction in disease severity has reflected in increased crop yield. The plots sprayed with Metalaxyl MZ 68WP + P. fluorescens has recorded the highest yield of 518.2 kg of dry beans ha-1 followed by 436.2 and 433.6 kg ha-1, respectively, in Mancozeb + P. fluorescens and Bordeaux mixture + P. fluorescens. The maximum disease severity was recorded in untreated control plots (46.2%) with a minimum yield of 337.3 kg ha-1. The highest net return of ` 62,007 was recorded in plots sprayed with Metalaxyl MZ 68WP + P. fluorescens sprayed plots. Thus, the integration of chemicals with a biological control agent was found to be promising not only in the management of pod rot disease but also in obtaining higher net returns in cocoa.